Evaluasi Website SIPENDUDUK dalam Meningkatkan Pelayanan Admnistrasi Kependudukan Disdukcapil di Kecamatan Rumbai Timur Kota Pekanbaru - Novita Rahayu; Ayshaadilla Putri; Elly Nielwaty (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
The administration of population services in Rumbai Timur District continues to face challenges following the regional expansion that required residents to update their civil documents. The SIPENDUDUK website was introduced to simplify digital submissions; however, its implementation has not been fully effective. A portion of the community, particularly older adults and individuals with low digital literacy, still struggles to navigate service flows and upload required documents. This study aims to evaluate the service quality of the SIPENDUDUK website in improving the effectiveness of civil administration services. A descriptive qualitative method was employed through observations and interviews with officers and service users. The findings indicate that although the website has facilitated administrative processes, its accessibility has not yet reached all user groups due to varying technological capabilities. The system shows adequate efficiency and stability, although several technical issues remain. Service security is maintained through controlled access and a simplified interface. User support is provided through direct assistance from the local office, including manual guidance and mobile outreach services. These results highlight that the success of digital services depends not only on system quality but also on user readiness. This evaluation is expected to contribute to improving the effectiveness, inclusiveness, and overall quality of population administration services in Rumbai Timur District.